The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1413-86702006000500004
|View full text |Cite
|
Sign up to set email alerts
|

Neurological profile and neurodevelopment of 88 children infected with HIV and 84 seroreverter children followed from 1995 to 2002

Abstract: This study evaluated the degree of neurological compromise in HIV-infected children accompanied by the outpatient clinic of infectious diseases and pediatric neurology of the Clinical Hospital of the Federal University of Paraná (UFPR) starting in 1995. Long-term progressive prospective and cross sectional study of 88 children infected by HIV and 84 seroreverter children, using data from general neurological examinations, neuroimaging procedures (brain CT scan) and neurodevelopmental tests (CAT/CLAMS and DENVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…This is not surprising, since much of CNS development occurs after birth, and the immature brains of children or adolescents exposed to HIV are highly vulnerable to pathologic agents. CNS disease in pediatric HIV patients manifested as static or progressive encephalopathy, with classic symptoms including delay or loss of major motor and mental milestones, and atrophy of cortical/subcortical regions and other abnormalities on CT scans (Drotar et al 1997; Epstein et al 1988; Schwartz and Major 2006; Tahan et al 2006; Ultmann et al 1985; Van Rie et al 2007). In developed countries, rates of HIV-1 vertical transmission have been reduced to 1–2%, from 40% in 1995 (Buchholz et al 2010; Van Dyke 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, since much of CNS development occurs after birth, and the immature brains of children or adolescents exposed to HIV are highly vulnerable to pathologic agents. CNS disease in pediatric HIV patients manifested as static or progressive encephalopathy, with classic symptoms including delay or loss of major motor and mental milestones, and atrophy of cortical/subcortical regions and other abnormalities on CT scans (Drotar et al 1997; Epstein et al 1988; Schwartz and Major 2006; Tahan et al 2006; Ultmann et al 1985; Van Rie et al 2007). In developed countries, rates of HIV-1 vertical transmission have been reduced to 1–2%, from 40% in 1995 (Buchholz et al 2010; Van Dyke 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-infected children, basal ganglia calcification is a common finding among patients with abnormal imaging. 25 These patients almost uniformly have developmental delay.…”
Section: Managementmentioning
confidence: 99%
“…3 The prevalence of these specific neurologic complications in children with HIV-1 is limited to a few studies (Table 1). [4][5][6][7][8][9][10][11][12][13] A systematic review of 6 studies in Sub-Saharan Africa reported severe motor impairment and moderate cognitive impairment at 18 months of age in HIV-1 infected children. 14 A study from the Democratic Republic of Congo showed that environmental factors contribute to developmental dysfunction.…”
mentioning
confidence: 99%